Monitoring of Individual Needs in Diabetes (MIND): baseline data from the Cross-National Diabetes Attitudes, Wishes, and Needs (DAWN) MIND study. - Snoek, F; Kersch, N; Eldrup, E; Harman-Boehm, I; Hermanns, N; Kokoszka, A; Matthews, DR; McGuire, B; Pibernik-Okanovic, M; Singer, J; de Wit, M; Skovlund, SE (2011)
OBJECTIVE: To test the feasibility and impact of implementing the computer-assisted Monitoring of Individual Needs in Diabetes (MIND) procedure, which is aimed at improving recognition and management of the psychological needs of diabetic patients in routine care. RESEARCH DESIGN AND METHODS: The MIND study was implemented in diabetes clinics across eight countries as part of the annual review. The computerized assessment covered emotional well-being (World Health Organization 5 Well-Being Index), diabetes-related distress (Problem Areas in Diabetes), life events, and the patient's agenda. Medical data were retrieved from the charts, and agreed-upon actions were recorded. RESULTS: Of 1,567 patients monitored using the MIND, 24.9% had either likely depression or high diabetes-related distress; 5.4% had both. Over 80% of these patients were newly identified cases, and 41% of patients with depression were referred to a mental health professional. CONCLUSIONS: Monitoring of well-being and diabetes-related distress as part of routine diabetes care is feasible and helps to identify and discuss unmet psychosocial needs.